CORRELATION OF TOTAL GDP AND NUMBER OF SMALL AND MEDIUM ENTERPRISES IN THE EU-28 - Mirjana Štaka (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
Micro, small and medium enterprises play a major role in the country's economic growth and development. The connection and correlation of GDP and the number of small and medium-sized companies represents a key not only economic but also social role of EU countries. This paper seeks to explore small and medium enterprises as an important role in economic growth and development. Micro, small and medium enterprises play a very important role in the economic development of the country, which is the reason for many studies and analyzes. In addition to contributing to gross domestic product creation, they also play a key social role as they reduce unemployment. The aim of this paper is to assess the relationship between the components of gross domestic product (GDP) and the development of small and medium enterprises (SMEs) in the EU-28 in the years 2009-2019. To achieve this goal, we reviewed the literature, presented statistical data that confirm the importance of these companies in economic development, such as: indicator of entrepreneurship (calculated as the number of SME companies per 1000 inhabitants), participation of SMEs in creating added value. We have presented this data for selected EU countries. Material and methods of work will be performed statistical analysis of data collected for SMEs in the EU and thus enable verification of the hypothesis set in the paper. Secondary data downloaded from the Eurostat site will be used. Based on the downloaded data and the application of a simple regression model, a universal and original model will be presented. Before presenting the model, a correlation will be made in order to present the comprehensiveness of the model. The model will be presented in the form of a function, which will have the value of parameters on the basis of which the influence of independent variables on dependent ones will be determined. The results and conclusions are presented at the end of the paper. The results of the research confirm the theoretical significance and role of small and medium enterprises, as well as the need for their internalization and growth into global market leaders. If the unemployment rate increases by 1 unit (if one person loses his job) in the EU, it will cause a decrease in total domestic value (GDP) by 0.509 units. Every new unemployed worker will cost the EU so much unproduced output and new added value. Assuming that there is no unemployment in the EU, ie that the rate is equal to 0, the EU would produce a gross domestic value of 16,135 euros (note: only the impact and the relationship between the unemployment rate and GDP is taken into account here). Thus, it is clear how much costs and effects unemployment has on the gross domestic product and economic policy of EU countries.
Keywords: GDP, development, small companies, growth, EU